Prognostic use of soluble fms-like tyrosine kinase-1 and placental growth factor in patients with coronary artery disease. (January 2016) - Sinning, Christoph; Schnabel, Renate B; Zeller, Tanja; Seiffert, Moritz; Rupprecht, Hans J; Lackner, Karl J; Blankenberg, Stefan; Bickel, Christoph; Westermann, Dirk
Background: Intention of the study is to assess the cardiovascular mortality of patients with coronary artery disease (CAD) with the biomarkers of angiogenesis PlGF and its endogenous inhibitor sFlt-1.Methods: The cohort included n = 1848 patients with CAD and 282 subjects without CAD. In 85 patients cardiovascular mortality, as combination of fatal myocardial infarction or any cardiac death, during a median follow-up duration of 3.9 years was reported.Results: In Kaplan–Meier curve analysis PlGF in rising thirds was not predictive regarding outcome (p = 0.54), the same was shown for sFlt-1 (p = 0.44). Cox regression for the fully adjusted model provided a hazard ratio (HR) of 0.8 (p = 0.18) for PlGF and for sFlt-1 a HR = 1.0 (p = 0.8).Conclusion: Our results point out that these biomarkers reflecting angiogenesis might not be suited to establish prognosis in CAD.